Sulfonated polyimide-clay thin films for energy application - Ali, F. (Bentham Science Publishers B.V., 2016)
Background: Sulfonated polyimides (SPIs) are considered as the promising alternatives to Nafion as membrane materials for the polymer electrolyte membrane (PEM). They generally exhibit high ionic conductivity, good mechanical properties, excellent thermal and chemical stabilities. The six-membered ring, naphthalenic anhydride-based SPIs, not only exhibit superior chemical and thermo-oxidative stabilities but are also more resistant to hydrolysis than their five-membered phthalic anhydride-based SPIs. The composites based on napthalenic polyimides are also significantly stable in high temperature environment and show better stability to hydrolysis. Incorporation of inorganic fillers into organic polymers has gained tremendous attention and these new materials are called organic-inorganic hybrids. Few patents related to the synthesis and performance PEM materials have been reviewed and cited. Keeping in view the importance of sulfonated polyimide based nanocomposites as potential membrane materials for PEM in fuel cell, we have synthesized SPIs clay based nanocomposite as potential membrane material. The objective of this work was to synthesize clay based SPIs thin films which could be used as membrane materials in PEM fuel cell for energy applications. Methods/Experimental: At the first step the nanometric sheets of vermiculite clay prepared via sonication was surface modified by grafting 3-APTES. Then the SPI was synthesized via one-step high temperature direct imidization method, which serve as a matrix material. The organo modified VMT was dispersed via sonication in the SPI matrix. Four different sets of organic-inorganic nanocomposite membranes thin films, having VMT contents in the range of 1 to 7 wt. were prepared by casting, curing and acidification route. Results: The synthesis of SPIs clay based thin films were carried out at three different steps and fully characterized. The synthesis of SPIs and SPIs clay based thin films were analyzed via different analytical techniques. The XRD analysis tells the successful dispersion of clay in SPI matrix. Different physiochemical tests were conducted for the analysis of these membranes such as water uptake, hydrolytic stability, ion exchange capacity (IEC), dimensional changes and oxidative stability, to check their suitability as membrane materials for PEM. The proton conductivity of these membranes were measured via impedance spectroscopy which discloses three different active regions responsible for proton conduction. The activation energies of the membranes were higher at lower temperature and reaches to 8.2 kJ/mol at higher temperature (90Â°C). Conclusion: The synthesis of sulfonated polyimide/clay (SPI/clay) based organic-inorganic nanocomposite membranes were achieved successfully. The membrane display good hydrolytic, thermal and oxidative stability at elevated temperature. The proton conductivity of the membrane display an increase together with the frequency but decreases with temperature. Therefore some more efforts are required to achieve high degree of functionalization of both organic and inorganic components, for the âfutureâ PEMs to avoid deterioration and to get improved performance. Â© 2016 Bentham Science Publishers.